Leachability of uranium and other elements from freshly erupted volcanic ash - Smith, David B.; Zielinski, Robert A.; Rose, William I. (Journal of Volcanology and Geothermal Research, 2003)
A study of leaching of freshly erupted basaltic and dacitic air-fall ash and bomb fragment samples, unaffected by rain, shows that glass dissolution is the dominant process by which uranium is initially mobilized from air-fall volcanic ash. Si, Li, and V are also preferentially mobilized by glass dissolution. Gaseous transfer followed by fixation of soluble uranium species on volcanic-ash particles is not an important process affecting uranium mobility. Gaseous transfer, however, may be important in forming water-soluble phases, adsorbed to ash surfaces, enriched in the economically and environmentally important elements Zn, Cu, Cd, Pb, B, F, and Ba. Quick removal of these adsorbed elements by the first exposure of freshly erupted ash to rain and surface water may pose short-term hazards to certain forms of aquatic and terrestrial life. Such rapid release of material may also represent the first step in transportation of economically important elements to environments favorable for precipitation into deposits of commercial interest. Ash samples collected from the active Guatemalan volcanoes Fuego and Pacaya (high-Al basalts) and Santiaguito (hornblende-hypersthene dacite); bomb fragments from Augustine volcano (andesite-dacite), Alaska, and Heimaey (basalt), Vestmann Islands, Iceland; and fragments of “rhyolitic” pumice from various historic eruptions were subjected to three successive leaches with a constant water-to-ash weight ratio of 4:1. The volcanic material was successively leached by: (1) distilled-deionized water (pH = 5.0–5.5) at room temperature for 24 h, which removes water-soluble gases and salts adsorbed on ash surfaces during eruption; (2) dilute HCl solution (pH = 3.5–4.0) at room temperature for 24 h, which continues the attack initiated by the water and also attacks acid-soluble sulfides and oxides; (3) a solution 0.05 M in both Na,CO, and NaHCO, (pH = 9.9) at 80°C for one week, which preferentially dissolves volcanic glass. The first two leaches mimic interaction of ash with rain produced in ...